Newton Diehl Baker papers - Baker, Newton Diehl, 1871-1937.
Correspondence, memoranda, minutes, speeches, writings, reports, newspaper articles, printed matter, and other papers relating primarily to Baker's post-World War I activities as the head of several business firms and of a number of organizations devoted to education, law and jurisprudence, and philanthropy, relief, and other types of human services. Firms and organizations represented include the American Judicature Society, Baltimore and Ohio Railroad, Cleveland Chamber of Commerce, Cleveland Trust Company, National Consumer's League, Phi Gamma Delta, and Woodrow Wilson Foundation. Includes material relating to Baker's post as U.S. secretary of war in Woodrow Wilson's cabinet during World War I.
Correspondents include the American Institute of Pacific Relations, John H. Clarke, Josephus Daniels, Norman H. Davis, Thomas Goddard Frothingham, Norman Hapgood, Ralph A. Hayes, Thomas W. Lamont, Esther Everett Lape, Walter Lippmann, Charles A. Mooney, George Foster Peabody, Franklin D. Roosevelt, Louis B. Selzer, James Thomson Shotwell, Samuel Ungerleider, George W. Wickersham, Edith Bolling Galt Wilson, and Howell Wright.
Microfilm edition of letterbooks (1896-1917) available
Microfilm edition of correspondence and other papers (1916-1922) available
Microfilm produced from originals in the Manuscript Division.
In part, typewritten transcripts and photocopies.
U.S. secretary of war, author, lawyer, and municipal official of Cleveland, Ohio.
Collection material in English.
Keywords: Clarke, John H. -- 1857-1945 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Davis, Norman H. -- 1878-1944 -- Correspondence; Frothingham, Thomas Goddard, -- 1865-1937 -- Correspondence; Hapgood, Norman, -- 1868-1937 -- Correspondence; Hayes, Ralph A. -- Correspondence; Lamont, Thomas W. -- 1870-1948 -- Correspondence; Lape, Esther Everett, -- 1881-1981 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; Mooney, Charles A., -- 1879-1931 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Selzer, Louis B. -- Correspondence; Shotwell, James T., -- 1874-1965 -- Correspondence; Ungerleider, Samuel -- Correspondence; Wickersham, George W. -- 1858-1936 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wright, Howell, -- 1882-1954 -- Correspondence; United States. -- War Department; American Institute of Pacific Relations -- Correspondence; American Judicature Society; Baltimore and Ohio Railroad Company; Cleveland Chamber of Commerce (Cleveland, Ohio); Cleveland Trust Company; National Consumers' League; Phi Gamma Delta; Woodrow Wilson Foundation; Banks and banking -- Ohio -- Cleveland; Consumers' leagues; Education -- Societies, etc; Human services; Justice, Administration of; Railroads -- Management; Trust companies -- Ohio -- Cleveland; World War, 1914-1918 -- United States; Cleveland (Ohio) -- Commerce; United States -- Politics and government -- 1913-1921.; Authors; Cabinet officers; Lawyers; Public officials -- Ohio